COVID-19 in the nervous system: physiopathology and neurological manifestations - Mendonça Filho, Valder Cavalcante Maia; de Oliveira, Amanda Gomes; Maia, Isabelle de Fátima Vieira Camelo; de Falcone, Ananda Carolina Moraes; Betini, Beatriz Gioppo; Rezende, Lucas Bruno; Magri Alves, Fernando Henrique (Arquivos de Neuro-Psiquiatria, 2023)
Background Coronavirus disease 2019 (COVID-19) is a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although respiratory manifestations have received greater visibility during the pandemic caused by this virus, numerous neurological complaints related to coronavirus 2 infection have been documented in several countries. These records suggest that this pathogen presents neurotropism, and it can cause different neurological conditions of varying intensity.Objective To investigate the ability of coronavirus 2 to invade the central nervous system (CNS) and its neurological clinical outcomes.Methods The present study consists in a comprehensive literature review of the records available in the PubMed, SciELO, and Google Scholar databases. The descriptors COVID-19, brain and physiopathology, associated with the Boolean operator AND, were used in the search. Regarding the inclusion and exclusion criteria, we selected the papers published since 2020 with the highest number of citations.Results We selected 41 articles, most of them in English. The main clinical manifestation associated with COVID-19 patients was headache, but cases of anosmia, hyposmia, Guillain-Barré syndrome, and encephalopathies were also described with considerable frequency.Conclusion Coronavirus-2 presents neurotropism, and it can reach the CNS by hematogenous dissemination and by direct infection of the nerve endings. It causes brain injuries through several mechanisms, such as cytokine storm, microglial activation, and an increase in thrombotic factors.
Keywords: COVID-19; Neurological Manifestations; Viral Tropism; Cytokine Release Syndrome